Effects of device settings and e-liquid characteristics on mouth-throat losses of nicotine delivered with electronic nicotine delivery systems (ENDS). (June 2023) - Hosseini, Sana; Gholap, Vinit; Halquist, Matthew S.; Golshahi, Laleh
Abstract: Currently it is not fully understood how the device settings and electronic liquid (e-liquid) composition, including their form of nicotine content, impact mouth and throat losses, and potentially lead to the variations in total nicotine delivery to the human lungs. An in situ size assessment method was developed for real-time measurements at the mouthpiece and outlet of a biorelevant mouth-throat to account for the dynamic nature of the aerosol. The aerosol size, temperature, and delivery through the mouth-throat replica and the exhaled aerosol between the puff intervals were measured at different wattages using various e-liquid compositions. The effects of body temperature and humidity on aerosol size and nicotine delivery were also explored to evaluate the importance of considering realistic in vivo conditions in in vitro measurements. Notably, in vitro tests with body temperature and humidity in mouth-throat model vs room conditions, resulted in larger aerosol size at the end of the throat (Dv50  = 5.83 ± 0.33 μm vs 3.05 ± 0.15 μm), significantly higher thoracic nicotine delivery (>90% vs 50–85%) potentially due to the lower exhaled amount (<10% vs 15–50%). Besides, higher VG/PG ratios resulted in significantly lower exhaled amount and higher mouth-throat nicotine deposition. One of the main outcomes of the study was finding significantly lower exhaled amount and higher thoracic nicotine delivery with nicotine salt form vs free-base. Considering body temperature and humidity also showed significant enhancement in nicotine delivery, so it is essential to account for biorelevant experimental conditions in benchtop testing. Highlights: Nicotine form, device settings, and composition of nicotine carriers in e-liquids affect respiratory nicotine delivery. Biorelevant conditions are critical in in vitro evaluation of nicotine delivery with electronic nicotine delivery systems. Biorelevant mouth-throat replicas, enabling in vitro measurement of regional deposition of nicotine, are practical tools.